TERRORIST THREAT IN RUSSIA: TRANSFORMATION OF CONFESSIONAL RELATIONSHIPS - KARABULATOVA, Irina; GALIULLINA, Svetlana; KOTIK, Ksenia (CENTRAL ASIA AND THE CAUCASUS, 2017)
Political dynamism and the rapidly developing informational and communicative Russian environment have pushed to the forefront the political linguo communicative technologies, which are increasingly and actively being used to control the communicative field in society, as well as the need for continuing the study of these technologies. They strongly affect the building up, organizing, and orienting of political activities of people and do impose on them certain political preferences. This means that they can be and are repeatedly used to address certain political tasks. The fast changes underway in Russia, the economic, political, and social transformations presuppose that mass consciousness and political behavior of its population should change accordingly: people should adapt themselves to new conditions; they should abandon the old and embrace new values and behavior patterns. As part of a political process, the religious factor becomes a social “siccative” of sorts: it may stabilize or destabilize a political situation. The subject we have discussed here is fairly urgent: the mechanisms and practices used to politicize religion should be identified for the sake of social stability and national security. Today, national security is further threatened by terrorism, proliferation of WMD, ethnic and religious conflicts, all sorts of pandemics, international crime, drug trafficking, etc. Having developed into a complicated, multifaceted, and open system, national security has already spread to domestic policies, geopolitics, and the economic, military, ethnic, regional, informational, and other spheres. The current religious situation in Russia—new religious movements, the growing number of followers of traditional religions, as well as radical Islam and religious terrorism—adds urgency to the need for understanding the fast and non-normative transformations of the religious scene. Terrorist ideology and terror, as its instrument, transform legal consciousness, lead to ideological and psychological distortions of legal values and the rule of law in general, and give rise to a new subculture, based on destruction and negation of the basic human values (legal thinking and ideology, legal institutions, economic order and business), rather than on protection of rights and freedoms, while ensuring adequate living standards.